An fMRI study of multimodal selective attention in schizophrenia. (November 2015) - Mayer, Andrew R.; Hanlon, Faith M.; Teshiba, Terri M.; Klimaj, Stefan D.; Ling, Josef M.; Dodd, Andrew B.; Calhoun, Vince D.; Bustillo, Juan R.; Toulouse, Trent
Abstract : Background: Studies have produced conflicting evidence regarding whether cognitive control deficits in patients with schizophrenia result from dysfunction within the cognitive control network (CCN; top-down) and/or unisensory cortex (bottom-up). Aims: To investigate CCN and sensory cortex involvement during multisensory cognitive control in patients with schizophrenia. Method: Patients with schizophrenia and healthy controls underwent functional magnetic resonance imaging while performing a multisensory Stroop task involving auditory and visual distracters. Results: Patients with schizophrenia exhibited an overall pattern of response slowing, and these behavioural deficits were associated with a pattern of patient hyperactivation within auditory, sensorimotor and posterior parietal cortex. In contrast, there were no group differences in functional activation within prefrontal nodes of the CCN, with small effect sizes observed (incongruent–congruent trials). Patients with schizophrenia also failed to upregulate auditory cortex with concomitant increased attentional demands. Conclusions: Results suggest a prominent role for dysfunction within auditory, sensorimotor and parietal areas relative to prefrontal CCN nodes during multisensory cognitive control.